A6.2 The NADPH oxidase 2 (NOX2) mediates an anti-inflammatory response to dead cell debris. (13th February 2015) - Hahn, J; Kienhöfer, D; Munoz, L; Holmdahl, R; Schett, G; Hoffmann, M
Abstract : Background and objectives: In the past, the production of reactive oxygen species (ROS) via the oxidative burst has been associated with the promotion of inflammation and tissue damage. However, recent research has implied that ROS are also important for regulation of inflammation and protection from autoimmune diseases. The focus of this project was to determine the involvement of the oxidative burst in the development of experimental lupus and its regulation of inflammatory properties. Methods: Lupus and arthritis (rupus) was induced by intraperitoneal injection of 0, 5 ml pristane oil in WT and Ncf1** mice carrying a mutation in one of the subunits of the phagocyte NADPH oxidase complex that abrogates ROS-production from NOX2. The progression of lupus/arthritis was followed during a six month period by serological markers and severity of organ involvement. Phagocytosis assays ( ex vivo ) were established to distinguish a differential uptake of cellular debris and latex beads in WT and Ncf1** mice via FACS analysis and fluorescence microscopy. The formation of neutrophil extracellular traps (NETs) was investigated in blood and peritonea. Results: After pristane-injection Ncf1** mice develop strongly elevated levels of typical lupus-autoantibodies, e.g. anti-dsDNA, anti-histone and anti-Sm/RNP, and arthritis. A certain amount of spontaneously occurring autoantibodies was also apparent in Ncf1** mice. Ncf1** mice also spontaneously developed signs of glomerulonephritis and exhibited glomerular deposits of complement and immunoglobulins, further exacerbated by injection of pristane. Interestingly, phagocytosis of secondary necrotic cells in Ncf1** mice was enhanced and skewed towards CD11b + Ly6c high monocytes, whereas there was no difference in the uptake of inert latex beads between Ncf1** and WT mice unless we coated the beads with immunoglobulin G. Furthermore, the ability of Ncf1** mice to create NETs and aggregated NETs was severely dampened. Conclusion: The Ncf1** mouse suffers from intensified experimental lupus/arthritis, characterised by autoantibodies directed against surface molecules of dead cells and aggravated organ involvement. The mechanics of the exacerbated autoimmune reaction could be associated to the atypical phagocytosis in Ncf1** mice, which demonstrated a skewed uptake of dead cell debris into inflammatory monocytes. The inability to form aggregated NETs could even prolong the inflammatory loop.